Optimasi Perbaikan Faktor Daya Dengan Pemasangan DC Reaktor Akan Mereduksi Harmonisa Di Inverter Motor Pendingin Air Industri - JAKARIYA - - (Sutet, 2019)
Three phase induction motor is widely used in the manufacturing industry because it has many advantages including easy maintenance, efficient use in various fields, durability and easy construction. This is behind the massive use of motorcycles. but the 3 phase induction motor also has disadvantages such as high starting currents and difficult to regulate speed. After emerging innovations regarding inverters as induction motor starters, the application of the device expanded because of its principle which regulates the number of motor frequencies slowly so as to make the 3-phase induction motor more efficient.The use of an inverter is indeed a solution to the problem of starting a 3-phase induction motor and regulating the motor speed, but behind the advantages there are disadvantages that the inverter produces a low power factor when operating the motor. The highest power factor when the inverter is working is 0.748, the lowest value is 0.478 and the average is 0.634. Based on this, it is necessary to optimize the improvement of the power factor to restore the condition of the motor to a standard power factor rating of 0.85.This research discusses the optimization of the improvement of the power factor by installing the DC reactor on the inverter unit and the results of an increase in the value of the highest power factor of 0.942, for the lowest value of 0.908 and an average of 0.927. the value of harmonics in the THD I1 (R) phase for the highest value of 184,230%, then the lowest value of 83,764% and for an average value of 119,329%